PFE-360-induced LRRK2 inhibition induces reversible, non-adverse renal changes in rats. (15th February 2018) - Andersen, Michael Aagaard; Wegener, Karen Malene; Larsen, Steen; Badolo, Lassina; Smith, Garrick Paul; Jeggo, Ross; Jensen, Poul Henning; Sotty, Florence; Christensen, Kenneth Vielsted; Thougaard, Annemette
Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder for which there is no existing therapeutic approach to delay or stop progression. Genetic, biochemical and pre-clinical studies have provided evidence that leucine-rich-repeat-kinase-2 (LRRK2) kinase is involved in the pathogenesis of PD, and small molecule LRRK2 inhibitors represent a novel potential therapeutic approach. However, potentially adverse target-related effects have been discovered in the lung and kidneys of LRRK2 knock-out (ko) mice and rats. It is unclear if the LRRK2 ko effect in the kidneys and lung is also induced by pharmacological inhibition of the LRRK2 kinase. Here, we show that treatment with the LRRK2 inhibitor PFE-360 in rats induces a morphological kidney phenotype resembling that of the LRRK2 ko rats, whereas no effects were observed in the lung. The PFE-360 treatment induced morphological changes characterised by darkened kidneys and progressive accumulation of hyaline droplets in the renal proximal tubular epithelium. However, no histopathological evidence of renal tubular injury or changes in the blood and urine parameters that would be indicative of kidney toxicity or impaired kidney function were observed after up to 12 weeks of treatment. Morphological changes were detected in the kidney after 2 weeks of treatment and were partially reversible within a 30 day treatment-free period. Our findings suggest that pharmacological LRRK2 inhibition may not have adverse consequences for kidney function.